Motivasi Belajar dalam Pandangan Abraham Maslow - Zahro, Shofiatus; Jannah, Thoriqotul (FKIP Universitas Islam Jember, 2023)
In everyday learning activities students really need motivation, especially external motivation to have a passion for learning. They are not enthusiastic during the learning process in class because they feel lazy. It takes passion and seriousness from students in understanding so much material and lessons. In every learning activity educators and families have a very important role to give a positive influence. There are many ways that can be done to revive the enthusiasm of students, including through a reward or praise for students who are diligent in learning. This method can provide encouragement to be more passionate in achieving their goals. Abraham Maslow's theory explains that individuals have needs such as learning, where these needs must be met and a learner is required to have a sense of having to learn.